Theory and practice of labor education of junior schoolchildren in extracourse activities - Galiya B. Sarmutdinova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper emphasizes the importance of junior schoolchilds labor education in extracurricular activities, a negative trend of developing generation underestimation is noted. The optimal transformation of the junior schoolchilds labor education of in extracurricular activities is determined. It is clarified that labor is the most important means of introducing schoolchild to universal, aesthetic and individual values. The results of theoretical analysis and practical experience, ways to eliminate the identified difficulties in the organization of labor education of junior schoolchild in extracurricular activities are presented. The functions and tasks of a teacher, a schoolchild and a parent that influence the labor education of a junior schoolchild in extracurricular activities are clarified. The paper highlights the functions of labor education: teaching, developing, educational. The main function of the teacher is the organization of interaction with junior schoolchildren and their parents, the integration of various types of activities (cognitive, gaming, labor), according to which cognitive processes develop (perception, thinking, memory, etc.), their ability to communicate and work together with the subjects. The solution of the problem: to study the theory of labor education and describe the experience of labor education of a junior schoolchild in extracurricular activities, required a phased solution of it, taking into account the moral standards of the junior schoolchild, certain rules of his behavior. At the first stage of experimental work, we recorded the acquired qualities of labor education of junior schoolchildren in situations of life activity that illustrate their attitude to society, the team, work, people, and themselves. And at the second stage, the features of the influence of labor activity on interpersonal communication were revealed, and on this basis the level of development of the team in labor activity was determined.